Pengaruh Pembiayaan Murabahah, Mudhorobah dan Musyarakah Terhadap Profitabilitas RoA BSM di Indonesia Periode 2015-2020 - Sarwono -; Novi Mubyarto; Rafidah - (ITB AAS INDONESIA Surakarta, 2023)
Mandiri Syariah Banks that previously only introduced alternative practices of Islamic Banking, but are now growing and developing by placing their position as a major player in the Indonesian economic arena. This research aims to examine the effect of Murabahah, Mudharabah and Musyarakah financing on Return On Assets profitability at Bank Syariah Mandiri in Indonesia for the 2015-2020 period. The sample data used is data from 2015 to 2020. To answer this research, the researchers used a quantitative research method. Data analysis used is descriptive statistical analysis and multiple linear regression. Based on the results of hypothesis testing, it can be explained that the effect of Murabahah financing (X1) has a significant effect, Mudharabah financing (X2) has no significant effect, and Musyarakah Financing (X3) has a significant effect.